2003
DOI: 10.1039/b301824p
|View full text |Cite
|
Sign up to set email alerts
|

Ozonolysis of phenols in aqueous solution

Abstract: In the ozonolysis of phenol in aqueous solution at pH 3, 7 and 10 the following products were quantified: catechol, hydroquinone, 1,4-benzoquinone, cis,cis-muconic acid, H2O2, 2,4-dihydroxybiphenyl and 4,4-dihydroxybiphenyl. At pH 10, material balance (products vs. phenol consumption) is obtained. Singlet dioxygen, O2(1 delta g), and .OH are formed as short-lived intermediates. The precursor of the latter, O3.-, and a phenoxyl radical is suggested to arise from electron transfer from phenol/phenolate to ozone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
200
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(226 citation statements)
references
References 63 publications
21
200
0
5
Order By: Relevance
“…For instance, phenolate ions are much more reactive toward O 3 than phenols, i.e., by a factor of ∼10 6 . 39 However, it is difficult to determine the amounts of conjugated ions of Tyr in our flowtube experiments. Local pH and exact pK a (of the phenolic hydrogen) values for the individual Tyr residues are hard to determine under these experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, phenolate ions are much more reactive toward O 3 than phenols, i.e., by a factor of ∼10 6 . 39 However, it is difficult to determine the amounts of conjugated ions of Tyr in our flowtube experiments. Local pH and exact pK a (of the phenolic hydrogen) values for the individual Tyr residues are hard to determine under these experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…According to this equation, ∼10 −5 to ∼10 −3 dissociated ions per residue should be present at pH 5−7, respectively. By a simple division of the rate constant of Tyr + O 3 calculated by the model in this study (∼6 × 10 5 −3 × 10 7 M −1 s −1 ) with the rate constant of phenolate + O 3 reported by Mvula and von Sonntag (1.4 × 10 9 M −1 s −1 ), 39 we may estimate that ∼4 × 10 −4 to ∼2 × 10 −2 of the reactive Tyr residues in BSA were present in the form of dissociated ions under the experimental conditions applied in this study, indicating neutral to slightly acidic pH in the flow tube experiments. Further, rate constants of Tyr + O 3 reported in the literature (0.7−2.8 × 10 6 M −1 s −1 in neutral pH, 52 and 7.2 × 10 7 M −1 s −1 in aqueous medium at 298 K calculated using variational transition state theory 37 ) are in fairly good agreement with our model results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that hydrogen peroxide can be generated during photocatalytic treatments 32 and also through direct ozone reactions [35,36,37]. The role of H 2 O 2 and O 3 involved in 33 photocatalytic reactions has been analyzed through the results depicted in Fig.7.…”
mentioning
confidence: 99%
“…The combined application 31 of ozone and TiO 2 photocatalysis, known as photocatalytic ozonation, leads to a 32 synergistic effect due to enhanced production of reactive oxygen species (ROS) such 33 as hydroxyl radicals in comparison with the application of either single ozonation or 34 single TiO 2 photocatalysis [7,8]. 35 In this study, the degradation of four herbicides and pesticides: diuron (DIU), o-36 phenylphenol (OPP), 2-methyl-4-chlorophenoxyacetic acid (MCPA) and terbuthylazine 37 (TBA), commonly found in water ecosystems, has been studied. Their molecular 38 structures can be found in Table S1 of the supplementary material.…”
Section: Introductionmentioning
confidence: 99%